Analysis of Critical Thinking Skills in Science Learning Through the Implementation of Project Based Learning Model Assisted by Animated Video Media in Elementary School Students - Ririen Dwi Puspitaningrum; Ivayuni Listiani; Hendra Erik Rudyanto (Postgraduate, University of Mataram, 2025)
This research analyzes elementary school students' critical thinking skills in science learning through Project-Based Learning (PjBL) model assisted by animated video media. Using a qualitative approach, the study was conducted at SDN Garon 01, Balerejo District, Madiun Regency, involving 28 sixth-grade students. Data were collected through participatory observation, in-depth interviews, and documentation from 12 primary informants, with analysis following the Miles, Huberman, and Saldana model. Results show that PjBL implementation with animated video media effectively develops students' critical thinking abilities in solar system material. Students demonstrated improved performance across six critical thinking aspects: interpretation, analysis, evaluation, inference, explanation, and self-regulation. Most students successfully analyzed astronomical information, evaluated materials for project creation, and synthesized knowledge from multiple sources. Animated video media enhanced learning by increasing student motivation, visualizing abstract astronomical concepts, and stimulating analytical questioning. The PjBL model facilitated learning through authentic problem-solving, collaborative group work, and hands-on experience in creating scientific models. Despite challenges including time constraints and varied student abilities, the integration of PjBL with animated video media significantly improved elementary students' critical thinking skills. These findings support the effectiveness of combining innovative pedagogical approaches with technology to develop higher-order thinking skills in elementary science education.